Psychosocial and cognitive determinants of health and risk behaviors In adolescence - Albuquerque, Carlos (2021)
Introduction: The adoption of health and risk behaviors is a complex and multifactorial process, related to adolescent development. However, this is still amatter of debate and reflection. Objective: Determine the effect of psychosocial and cognitive variables on health and risk behaviors evidenced by adolescents. Methods: Quantitative, descriptive-correlational study, in a cross-sectional cohort, in a sample of 829 adolescents, mostly female (53.92%). Data werecollected through a sociodemographic form and scales measured and validated for the Portuguese population (Piers-Harris Children’s Self-Concept Scale;Satisfaction with Social Support Scale; Assertiveness Scale of the Interpersonal Behavior Inventory; Scale of Locus de Health Control). Results: Statistically significant effects in predicting health and risk behaviors in adolescents seem to occur due to the presence of interaction effects between psychosocial and cognitive variables. Specifically, behaviors appear to be associated, above all, with the interaction effect between self-concept and attitudes towards health. In other words, the meaning of this association suggests that adolescents with better behavioral self-concept and a more adequate preventiveattitude are the ones with better health-related behaviors. Conclusion: It is noted that it is necessary to increase self-concept and improve attitudes towards the health of adolescents, so an integrated and appropriatedevelopment strategy for health promotion in a school context seems to emerge from this study.